Community perception differences regarding ecosystem goods and services in reservoir landscapes with and without inter-basin water transfer: Implications for the Sustainable Development Goals - Lucianna Marques Rocha Ferreira; Franciely Ferreira Paiva; Maria Eduarda Santana Veríssimo; Lívia Maria Osório de Sousa; Evaldo de Lira Azevêdo; José Etham de Lucena Barbosa; Joseline Molozzi (PLoS ONE, 2025)
Water is a fundamental ecosystem good and service (EGS) for supporting life on Earth. In arid and semiarid regions, water scarcity is a recurring problem that limits socioeconomic activities and the achievement of Sustainable Development Goals (SDGs). Inter-basin water transfer (IBWT) schemes have been employed to alleviate the impact of water scarcity. This study explored how IBWT affects the perceptions of riverside communities regarding EGSs within a semiarid reservoir landscape, assessing the interplay between perceived EGSs, SDGs, and land use and land cover (LULC). Furthermore, this study evaluated the influence of sociodemographic factors on these perceptions. The study was conducted across eight reservoir landscapes, with four reservoirs receiving and four not receiving IBWT. Semi-structured forms and participatory mapping were used to discern and map the EGSs as perceived by the communities. These perceived EGSs were then linked to the SDGs. The communities identified 29 EGSs classes (provision, regulation and maintenance, and cultural services) in the set of reservoir landscapes studied. Provision services were the most frequently mentioned (78.53%). It was found that educational level significantly influenced community perceptions of EGSs (p = 0.003). Particularly, provisioning services associated with the LULC water were mentioned more frequently than other LULC types (p = 0.02). Forest formations were the primary providers of regulation and maintenance services compared to water bodies, land use mosaics, and floodplains (padjusted = 0.02) and received more citations for cultural services than land use mosaics and built-up areas (padjusted = 0.02). Cultural services were predominantly acknowledged by individuals residing near reservoirs that received IBWT (p = 0.006), while those near non-IBWT reservoirs more often reported regulation and maintenance services (p = 0.003). Provisioning services were strongly linked to the SDGs (p = 0.0001) and can substantially facilitate SDGs attainment, notably impacting goals 1, 2, 3, 12, and 15. The presence of IBWT significantly shapes community perceptions of reservoir landscape elements in the semiarid region.